The Effect of Combination Ringer's Solution Diluents on Semen Quality and DNA Damage of Gaga Chicken Sperm - Fisabilillah, Fairus Vavang; Khaeruddin, Khaeruddin; Yekti, Aulia Puspita Anugra; Prayogi, Heni Setyo; Wahjuningsih, Sri (Faculty of Animal Science, Universitas Brawijaya, 2026)
Gaga chicken is an indigenous Indonesian poultry genetic resource with important cultural and germplasm value. However, its population is threatened by genetic dilution from uncontrolled crossbreeding. This study aimed to evaluate the effectiveness of Ringer-based extenders supplemented with egg yolk or skim milk in maintaining the quality of Gaga chicken spermatozoa following cryopreservation. Semen was collected from sexually mature Gaga roosters using the massage method, and each ejaculate was divided into four equal aliquots (split-sample design) to minimize biological variation. A total of 40 experimental units (4 treatments × 10 replications) were analyzed in a completely randomized design: TI (Ringer Lactate + 10% egg yolk), T2 (Ringer Acetate + 10% egg yolk), T3 (Ringer Lactate + 6% skim milk), and P4 (Ringer Acetate + 6% skim milk). Samples were equilibrated at 5 °C for 2 h and cryopreserved in liquid nitrogen (?196 °C). Parameters observed included motility, viability, DNA damage before freezing and after thawing, recovery rate, and DNA fragmentation. Cryopreservation significantly reduced post-thaw motility and viability (P < 0.05), whereas DNA damage did not differ among treatments (P > 0.05). Treatment TI resulted in the highest post-thaw motility (31.00 ± 1.63%) and viability (52.72 ± 2.57%), significantly higher than P4 (P < 0.05), and produced the highest recovery rate (37.21 ± 2.10%) (P < 0.05). In conclusion, Ringer Lactate supplemented with 10% egg yolk is the most effective extender for maintaining sperm quality during cryopreservation and represents a practical approach for conserving indigenous chicken genetic resources.